Il tabarro - Puccini, Giacomo 1858-1924 (Dynamic Srl, 2020)
The production is a new staging of the Teatro del Maggio Musicale Fiorentino. It is one of the three one-act operas that compose Giacomo Puccini₂s Il Trittico. Michele is married to young Giorgetta and shares with her a life full of hardships on a barge over the river Seine. She is in love with Luigi, a young longshoreman hired by her husband during the loading of the barge